Dietary intake in the early years and its relationship to BMI in a bi-ethnic group: the Born in Bradford 1000 study. Issue 12 (2nd April 2018) - Mahoney, Samuel; Bryant, Maria; Sahota, Pinki; Barber, Stuart
Abstract: Objective: To assess relationships between dietary intake at age 12, 18 and 36 months and BMI Z -scores at age 36 months in a bi-ethnic group. Design: A prospective cohort study comparing cross-sectional and longitudinal data. Exposures included dietary intake at 12, 18 and 36 months (FFQ) with an outcome of BMI Z -score at age 36 months. Setting: Born in Bradford 1000 study, Bradford, UK. Subjects: Infants at age 12 months ( n 722; 44 % White British, 56 % Pakistani), 18 months ( n 779; 44 % White British, 56 % Pakistani) and 36 months ( n 845; 45 % White British, 55 % Pakistani). Results: Diet at age 12 months was not associated with BMI Z -score at age 36 months. Higher consumption of vegetables at 18 and 36 months was associated with a lower BMI Z -score at 36 months (model coefficient (95 % CI): −0·20 (−0·36, −0·03) and −0·16 (−0·31, −0·02), respectively). Higher consumption of high-fat chips at age 36 months was associated with a lower BMI Z -score at age 36 months (−0·16 (−0·32, 0·00)). Overall, White British children had higher 36-month BMI Z -scores than Pakistani children (adjusted mean difference (95 % CI): 0·21 (0·02, 0·41)). Conclusions: Our findings indicate that dietary intake at 18 and 36 months was somewhat related to BMI Z -score at age 36 months and suggest the importance of early interventions aimed at establishing healthy eating behaviours.